2022
DOI: 10.1038/s41467-022-32060-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing of photonic colloidal glasses into objects with isotropic structural color

Abstract: Structural color is frequently exploited by living organisms for biological functions and has also been translated into synthetic materials as a more durable and less hazardous alternative to conventional pigments. Additive manufacturing approaches were recently exploited for the fabrication of exquisite photonic objects, but the angle-dependence observed limits a broader application of structural color in synthetic systems. Here, we propose a manufacturing platform for the 3D printing of complex-shaped object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…The structural color of a colloidal crystal mainly originates from the Bragg reflection at visible light, while the structural color of a colloidal amorphous array is more complicated and depends on diverse scattering effects such as Mie resonances. 30,31 Many meaningful research works demonstrate that the selective reflection of a colloidal amorphous array is the function of the diameter and reflective index of colloidal particles. 26,29,30,33,34 The reflected wavelength center can be roughly described by eqs 1 and 2:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural color of a colloidal crystal mainly originates from the Bragg reflection at visible light, while the structural color of a colloidal amorphous array is more complicated and depends on diverse scattering effects such as Mie resonances. 30,31 Many meaningful research works demonstrate that the selective reflection of a colloidal amorphous array is the function of the diameter and reflective index of colloidal particles. 26,29,30,33,34 The reflected wavelength center can be roughly described by eqs 1 and 2:…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Many meaningful research works demonstrate that the selective reflection of a colloidal amorphous array is the function of the diameter and reflective index of colloidal particles. 26,29,30,33,34 The reflected wavelength center can be roughly described by eqs 1 and 2:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently 3D printing of colloidal particles with isotropic coloration was successful. [34] Here researchers have shown that silica particles mixed with a co-polymer and carbon black can be optimized to have the right consistency to prepare an ink for extrusion. [34] Such an ink can be extruded from a nozzle to obtain complex geometries.…”
Section: Pressing Additive Manufacturing Roll-to-roll Tapecastingmentioning
confidence: 99%